Rhodium(III)-Catalyzed Enantioselective Benzamidation of Cyclopropenes - Shaaban, Saad; Li, Houhua; Merten, Christian; Antonchick, Andrey P.; Waldmann, Herbert (Synthesis, 2021)
Cyclopropylamines are characteristic structural motifs found in a variety of natural products and pharmaceuticals and therefore engaging targets for the development of new methods for their synthesis. Herein the synthesis of enantioenriched cyclopropylamines through catalytic enantioselective C–H functionalization using a chiral RhJasCp complex is reported. The reaction proceeds under mild conditions with high enantiocontrol. This reaction enables access to cyclopropylamines with three contiguous stereocenters originating from the corresponding cyclopropenes.
Keywords: rhodium catalysis; cyclopropenes; chiral cyclopentadiene; C–H activation; cyclopropylamine